[OP.4B.03] CIRCULATING ALDOSTERONE LEVELS ARE ASSOCIATED WITH CONCENTRIC LEFT VENTRICULAR GEOMETRY IN ESSENTIAL HYPERTENSIVE PATIENTS. (September 2016) - Mule', G.; Nardi, E.; Guarino, L.; Morreale, M.; Altieri, D.; Geraci, G.; Guarneri, M.; Cacciatore, V.; Cerasola, G.; Cottone, S.
Abstract : Objective: Sound evidence indicates that aldosterone has a fundamental role in determining functional and structural changes in the heart. Moreover, it has been observed that high plasma aldosterone concentration (PAC) is related to the development of congestive heart failure and to cardiovascular mortality. However, previous studies on the association between circulating aldosterone levels and left ventricular (LV) mass (LVM) and LV geometry, in subjects without primary aldosteronism yielded conflicting results. The aim of our study was to evaluate in patients with essential hypertension the relationships of PAC with LV mass and geometry, and to asses the influence of gender on these relationships. Design and method: A total of 478 subjects (men: 63%; mean age 44 ± 12 years) with untreated essential hypertension were enrolled. The measurements included 24-h blood pressure (BP) readings, plasma renin activity (PRA) and PAC, obtained by radioimmunoassay and an echocardiogram. For its skewed distribution PAC was log transformed and expressed as median value and interquartile range. Results: PAC was significantly lower (p < 0.01) in subjects with normal LVM indexed for body surface area (BSA) (n = 272) [7.5 (5.3–12.4)], as compared to those with concentric remodeling (n = 61) [10.2 [7.95–14.5)], to the patients with eccentric LV hypertrophy (LVH) (n = 90) [9.8 (6.9–12.9)], and to the subjects with concentric LVH (n = 61) [11.3 (7.7–16.6 ng/ml)]. Significant correlations of Log (PAC) with LVM, either indexed for BSA (r = 0.20; p < 0.0001), or for height 2.7 (r = 0.21; p < 0.0001) and with relative wall thickness (RWT) (r = 0.18; p < 0.0001) were found. These correlations were similar in men and in women and remained statistically significant in multiple regression analyses, even after adjustment for potential confounding factors (all p < 0.01). Conclusions: Our results seem to suggest that in essential hypertensive patients circulating aldosterone levels are independently associated with concentric LV geometry, without gender-related differences.